Education and outreach by the Antarctic Treaty Parties, Observers and Experts under the framework of the Antarctic Treaty Consultative Meetings. (18th December 2018) - Xavier, José C.; Mateev, Dragomir; Capper, Linda; Wilmotte, Annick; Walton, David W. H.
Abstract: The development of formal discourse about education and outreach within the Antarctic Treaty Consultative Meetings (ATCM), and the influence of major international activities in this field, are described. This study reflects on the ATCM Parties' approach to implementing the ambition of the Protocol on Environmental Protection to the Antarctic Treaty Article 6.1.a, to promote the educational value of Antarctica and its environment, and examines the role of workshops and expert groups within the Scientific Committee on Antarctic Research (SCAR), the International Union for the Conservation of Nature (IUCN), and the Council of Managers of National Antarctic Programmes. These early initiatives, which emerged in the 1990s, were a prelude to the development and implementation of a large number of International Polar Year (IPY) education and outreach programmes. The establishment of an Antarctic Treaty System Intersessional Contact Group, and an online forum on education and outreach during the 2015 ATCM in Bulgaria, is a legacy of IPY and is the next step in fostering collaboration to engage people around the world in the importance and relevance of Antarctica to our daily lives.